Study on the disease burden of lip and oral cancer attributable to tobacco use: based on the 2021 Global Burden of Disease study - Shu, Shu’ang; Weng, Shuping; Gu, Jinchao (Frontiers in Oncology, 2025)
BackgroundTo analyze the global, regional, and national epidemiological trends of lip and oral cancer (LOC) diseases attributable to tobacco from 1990 to 2021, with an emphasis on health inequalities.MethodsUtilizing the Global Burden of Disease (GBD) 2021 study, we evaluated the temporal trends in tobacco-attributable LOC mortality and disability-adjusted life years (DALYs). We further analyzed how LOC mortality and DALYs varied by age, period, and birth cohort. The Bayesian Age-Period-Cohort (BAPC) model was employed to project trends from 2021 to 2050. Additionally, decomposition analysis was conducted to identify key drivers of change, and health inequalities were assessed. Finally, frontier analysis was performed across global countries and regions.ResultsFrom 1990 to 2021, tobacco-attributable LOC mortality and DALYs exhibited a significant declining trend globally (estimated annual percent change of -0.49 and -0.61, respectively). Population growth was the primary driver of increasing burden, while epidemiological transition mitigated the burden. Projections indicate that the burden will continue to decline by 2050, with low socio-demographic index (SDI) regions experiencing significantly higher burden compared to high SDI regions. Age effects showed a stepwise increase in mortality with advancing age, period analysis confirmed the sustained reduction in tobacco-related harm, and cohort studies revealed significantly lower risk among later-born populations. Cross-national analysis revealed a narrowing gap in burden between high and low SDI countries, yet countries such as Pakistan and Palau still exhibit substantial health benefit gaps.ConclusionAlthough the global burden of tobacco-attributable LOC diseases shows a slow declining trend, low and middle SDI regions continue to maintain high burden levels. Strengthening tobacco control strategies in these regions are essential to narrow health disparities.